(untitled) (Nepalese Medical Journal, 2019)
Erectile dysfunction affects a growing number of men with a significant impact on social function. The cause may be medical and psychological both. Of many risk factors for erectile dysfunction, hyperthyroidism can lead to increased total testosterone by an increase in sex hormone-binding globulin secreted from the liver. Here, we present a case of an adult male with a high total testosterone level who complained of erectile dysfunction. On a complete review of medical history and additional laboratory tests, the diagnosis of hyperthyroidism leading to increased total testosterone was made. The complete review of the patient’s history before hormonal analysis helps to troubleshoot the mismatch between clinical symptoms and laboratory results.